Comparison between PID and fuzzy regulator for control evaporator plants - Hrama, Mykhailo; Sidletskyi, Victor; Elperin, Igor (My University, 2019)
In this paper, a comparison is made between FID and fuzzy controller. The purpose of the study is to determine when the use of which type of regulation will achieve the best indicators of quality control for the regulation of the evaporator. The regulation of such responsible parameters as levels of concentrated juice in the evaporator's buildings, which directly affect the quality and cost of manufactured products, is carried out. First, a mathematical model was developed in the space of states in the Matlab environment and results were obtained with respect to the variation of the problem relative to the initial conditions and with respect to perturbation. Secondly, a mathematical model with a PIDregulator was developed and transient processes for control circuits in all control channels were obtained. Thirdly, a mathematical model with a fuzzy controller was developed and transient processes for control circuits in all control channels were obtained. When comparing the mathematical model with PID and the fuzzy controller, it was concluded that the use of neuro-fuzzy regulation is more appropriate as it leads to an increase in the qualitative parameters of the process compared with the system with PID regulators.
Keywords: sugar juice; mathematical model; evaporator plant; neuro-fuzzy regulation; кафедра інформаційних технологій, штучного інтелекту і кібербезпеки; кафедра автоматизації та комп'ютерних технологій систем управління ім. проф. А.П. Ладанюка